Diversity and Structure of the phytoplankton of Lake Ahémé, a part of the Ramsar 1017 (Bénin) - Olodo, Isabella Yasmine I. B.; ABOU, YOUSSOUF (My University, 2020)
This study aims to assess the phytoplankton community of Lake Ahémé, subject to anthropogenic pressures. For this purpose, eight sites were sampled from September 2014 to October 2016. A total of 274 taxa were recorded and were mainly dominated by Bacillariophyceae (54%), followed by Chlorophyceae (12.77%), Cyanophyceae (10.22%), Euglenophyceae (9.49%), Conjugatophyceae (7.66%), Trebouxiophyceae (2.18%), Dinophyceae (1.82%), Xanthophyceae (0.73%), Ulvophyceae (0.73%), Chrysophyceae (0.36%). Overall, diversity was high during the long wet season and low during the short dry season, with imbalanced distribution of phytoplankton taxa over the study period. Biodiversity indices varied throughout seasons : between 4 and 16 for Margalef index, between 1.2 and 3 bits for Shannon index, between 0.46 and 0.9 for Simpson index, between 0.22 and 0.72 for Berger-Parker index and between 0.04 and 0.15 for evenness index. The particular abundance of diatoms observed is due to strong mineralization of the lake at the time of the study. These observations suggest that phytoplankton diversity and structure can be used in conjunction with physical and chemical indicators to assess water quality.
Keywords: Lake Ahémé; Phytoplankton; Eutrophication; Structure